Natural killer cells and BNT162b2 mRNA vaccine reactogenicity and durability - Graydon, Elizabeth K.; Conner, Tonia L.; Dunham, Kim; Olsen, Cara; Goguet, Emilie; Coggins, Si’Ana A.; Rekedal, Marana; Samuels, Emily; Jackson-Thompson, Belinda; Moser, Matthew; Lindrose, Alyssa; Hollis-Perry, Monique; et al. (Frontiers in Immunology, 2023)
Natural killer (NK) cells can both amplify and regulate immune responses to vaccination. Studies in humans and animals have observed NK cell activation within days after mRNA vaccination. In this study, we sought to determine if baseline NK cell frequencies, phenotype, or function correlate with antibody responses or inflammatory side effects induced by the Pfizer-BioNTech COVID-19 vaccine (BNT162b2). We analyzed serum and peripheral blood mononuclear cells (PBMCs) from 188 participants in the Prospective Assessment of SARS-CoV-2 Seroconversion study, an observational study evaluating immune responses in healthcare workers. Baseline serum samples and PBMCs were collected from all participants prior to any SARS-CoV-2 infection or vaccination. Spike-specific IgG antibodies were quantified at one and six months post-vaccination by microsphere-based multiplex immunoassay. NK cell frequencies and phenotypes were assessed on pre-vaccination PBMCs from all participants by multi-color flow cytometry, and on a subset of participants at time points after the 1 st and 2 nd doses of BNT162b2. Inflammatory side effects were assessed by structured symptom questionnaires, and baseline NK cell functionality was quantified by an in vitro killing assay on participants that reported high or low post-vaccination symptom scores. Key observations include: 1) circulating NK cells exhibit evidence of activation in the week following vaccination, 2) individuals with high symptom scores after 1 st vaccination had higher pre-vaccination NK cytotoxicity indices, 3) high pre-vaccination NK cell numbers were associated with lower spike-specific IgG levels six months after two BNT162b2 doses, and 4) expression of the inhibitory marker NKG2A on immature NK cells was associated with higher antibody responses 1 and 6 months post-vaccination. These results suggest that NK cell activation by BNT162b2 vaccination may contribute to vaccine-induced inflammatory symptoms and reduce durability of vaccine-induced antibody responses.